2020
DOI: 10.32615/ps.2020.038
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane leaf photosynthetic light responses and their difference between varieties under high temperature stress

et al.

Abstract: Leaf photosynthetic light response (PLR) of six sugarcane (Saccharum officinarum L.) varieties with a high sugar content was measured in the field. PLR curves were fitted by the rectangular hyperbola (RH) model, the nonrectangular hyperbola (NRH) model, and the Ye model, respectively. Photoinhibition occurred under warm and humid environment for all tested sugarcane varieties except for GT02-467 with the photosynthetic rate reduced significantly. The Ye model was the best for PLR curve fitting, especially when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…This study found that with increasing temperature, F m decreased, suggesting that high temperature resulted in the changes in cystoid membrane structure and organization. F v /F m is used to measure the maximum efficiency of PSII ( Liu et al., 2020 ). A decrease in F v /F m is often observed when plants are in a stress state, which represents impaired PSII function ( Guidi et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study found that with increasing temperature, F m decreased, suggesting that high temperature resulted in the changes in cystoid membrane structure and organization. F v /F m is used to measure the maximum efficiency of PSII ( Liu et al., 2020 ). A decrease in F v /F m is often observed when plants are in a stress state, which represents impaired PSII function ( Guidi et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…4.12 [118] software with the packages "ggbeeswarm" [119], "ggplot2" [120], "ggpubr" [121], and "minpack.lm" [122]. The net photosynthetic rate per unit area of leaf (P n µmol m −2 s −1 ) was assumed to be expressed by a nonrectangular hyperbola [19,123,124]:…”
Section: Discussionmentioning
confidence: 99%